Smart engineering of gold nanoparticles to improve intestinal barrier penetration - Kim, Hyung Shik; Lee, Dong Yun (Journal of industrial and engineering chemistry (Seoul, Korea), 2021)
[Display omitted] Overcoming the harsh environment and epithelial barrier of the gastrointestinal (GI) tract is an important challenge for orally administered nanodrugs. Among the various nano-sized drug delivery systems, gold nanoparticles (AuNPs) possess unique characteristics that make them promising candidates for improving drug bioavailability. A profound understanding of the GI tract microenvironment and the mechanisms of nanoparticle transportation through the intestinal epithelium is required to develop an effective oral drug delivery system. Moreover, the physicochemical properties of AuNPs, including their size, surface charge, rigidity, and shape, are relevant factors that affect the penetration processes. In this review, we describe the nanotechnologies that can be incorporated into AuNPs to efficiently target intestinal epithelial cells, penetrate mucus barriers, and respond to specific stimuli. Thus, we provide a comprehensive description of AuNPs to formulate a rational and effective engineering strategy to overcome the GI tract barriers.